Urgensi Pembentukan Sopan Santun Anak Melalui Model Pembelajaran Islamic Parenting di TK Islam Pancor Kopong - arfini, baiq desy; Hamdan, Hamdan; Junaidi, M; Iswandi, Lalu (khatulistiwa, 2024)
Islamic parenting is an Islamic parenting style. One of the Islamic principles that will be implemented at the Pancor Kopong Islamic Kindergarten is Manners. The phenomenon of students who are less polite towards their teachers and parents, and less polite towards their peers. So that children in the school environment do not have a polite attitude towards their school friends, including what happens to children around Pancor Kopong Hamlet, Pringgasela Village. It is interesting to study such issues in more depth, which is what underlies this research with the title "The Urgency of Forming Children's Manners through the Islamic Precenting Learning Model in the Pancor Kopong Islamic Kindergarten." This research uses qualitative research using descriptive methods. The location of this research was in Pancor Kopong, and the research subjects were children aged 5-6 years. This research is planned for October 16 2023 in the odd semester of the 2023/2024 academic year. The research methods are observation, interviews and documentation. The results of this research have a positive impact on children, by providing habituation or teaching children how to behave politely towards older people, people around them, parents and teachers.